2015
DOI: 10.1038/aps.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 is involved in decreased bone formation in aged apolipoprotein E-deficient mice

Abstract: In contrast to young apoE(-/-) mice, aged apoE(-/-) mice showe lower bone mass than age-matched WT mice. Long-lasting exposure to ox-LDL decreases the expression of Sirt1 and Runx2 in BMSCs, which may explain the decreased bone formation in aged apoE(-/-) mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…Cellular lipoprotein uptake is dependent on the interaction of their protein moieties, such as apolipoprotein E (ApoE), a 34 kDa glycoprotein, which plays a central role in lipoprotein metabolism, with endocytotic cell surface lipoprotein receptors. Over the last few decades, numerous studies have confirmed apoE regulated bone metabolism in mice (10)(11)(12)(13), but the mechanism is still undefined. One possible molecular explanation was provided by a series of experiments that characterized the role of apoE in the uptake of triglyceride-rich lipoproteins (TRL) and TRL-associated vitamin K into osteoblasts (10).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular lipoprotein uptake is dependent on the interaction of their protein moieties, such as apolipoprotein E (ApoE), a 34 kDa glycoprotein, which plays a central role in lipoprotein metabolism, with endocytotic cell surface lipoprotein receptors. Over the last few decades, numerous studies have confirmed apoE regulated bone metabolism in mice (10)(11)(12)(13), but the mechanism is still undefined. One possible molecular explanation was provided by a series of experiments that characterized the role of apoE in the uptake of triglyceride-rich lipoproteins (TRL) and TRL-associated vitamin K into osteoblasts (10).…”
Section: Introductionmentioning
confidence: 99%
“…This may have contributed to the bone loss in the aged apoE −/− mice seen in our previous study [29]. Statins have been proven to have a preventive effect on ageing through intervention with Sirt1 [49].…”
Section: Discussionmentioning
confidence: 61%
“…All samples were collected, and the Western blot was conducted as previously described [29]. The primary antibodies used were rabbit anti-Sirt1 (Cat.No:13161-1-AP;1:2000; Proteintech, Rosemont,USA), mouse anti-Runx2 (Cat.No:ab54868;1:1000; Abcam, CA, USA), and mouse anti-GAPDH (Cat.No:KC-5G4;1:10,000;…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Therefore, the stimulation of the BMP–Smad1/5/8–Runx2 signalling axis promotes osteogenic differentiation and bone remodelling in age‐related diseases (Chen et al., ). Previous studies suggest that SIRT1 and 6 promote osteogenic differentiation and bone formation via modulating the BMP signalling pathway in mesenchymal stem cells (Chen et al., ; Hong et al., ; Zhang et al., ). Our data also indicate that the expression of SIRT1 and 6 was significantly increased by IR and CR in RANKL‐treated BMMs.…”
Section: Discussionmentioning
confidence: 98%